Applicability of the free field Sustained Auditory Attention Ability Test (SAAAT) - Feniman, Mariza Ribeiro; Rissatto, Ariane Cristina Sampaio; Lauris, José Roberto Pereira; Mondelli, Maria Fernanda Capoani Garcia (International Archives of Otorhinolaryngology, 2012)
Introduction: The attention is an underlying neuropsychology function to all the cognitive processes. The auditory deficiency compromises the normal development of the child, modifying diverse auditory abilities, including the attention.Objective: to compare the performance of children in the Test of the Ability of Auditory Attention Support, as for the different forms of application (auricular phones and free field), sort and, application order.Method: 40 children (7 years old) voluntary with typical development had participated, divided in two groups: G1 and G2, composites of 20 children each. The application of the THAAS in the G1 if gave first with auricular phones and after that in free field and the G2 the process was inverse. The evaluation consisted in: specific questionnaire, auditory tests and application of the THAAS.Results: It did not have significant difference how much to the sort. For the THAAS with phones, the G1 presented greater amount of errors of carelessness and total punctuation. For the THAAS in field it had a significant difference of the G2 for the monitoring decrease. How much to the application form, the G1 demonstrated a bigger number of errors when it was used phones. The G2 did not demonstrate difference.Conclusion: It had viability in the application of the THAAS in Free Field, being able to be adopted the same used normative values for the conventional way of evaluation.
Keywords: hearing; attention; child